Mortality outcome and predictive risk factors for death in patients with heart failure and reduced ejection fraction who declined implantable cardioverter defibrillator implantation in Singapore. Issue 5 (18th August 2018) - Khoo, Chun Yuan; Allen, John Carson; Chia, Shaw Yang; Chan, Laura Lihua; Lim, Choon Pin; Sim, David; Ching, Chi Keong
Abstract: Background: There have been conflicting data regarding the risk of sudden cardiac death (SCD) in Asian population with reduced left ventricular ejection fraction (LVEF). We aim to study mortality outcome and its risk predictors in patients with reduced LVEF who declined an implantable cardioverter defibrillator (ICD) implantation and assess whether current ICD guidelines for primary prevention are applicable to the population in Singapore. Methods: This prospective observational study involved 240 consecutive patients who fulfilled the ACC/AHA/HRS criteria for ICD implantation for primary prevention of SCD but declined ICD implantation. Baseline characteristics and mortality outcomes through May 2017 were collected via case‐note review after a mean follow‐up of 44.8 ± 16.6 months. Results: Majority of our patients were Chinese (71.3%), followed by Malays (16.2%) and Indians (10.8%). Mean age (±SD) was 61 ± 10 years, and 84% were male. Majority were in New York Heart Association (NYHA) functional classes I (46.7%) and II (46.3%). Over a mean follow‐up of 44.8 ± 16.6 months, all‐cause mortality rate was 34.6%. Diabetes mellitus (HR = 1.57; 95% CI, 1.01‐2.44; P = 0.047) and chronic kidney disease (CKD; HR = 1.95; 95% CI, 1.17‐3.23; P = 0.010) were independent predictors of mortality. Patients in NYHA classes II (HR = 2.15; 95% CI, 1.32‐3.50; P = 0.002) and III (HR = 2.82; 95% CI, 1.34‐5.96; P = 0.007) showed higher risk of death. Conclusion: The mortality rate was comparable with major primary prevention trials. ICD guideline recommendations for primary prevention may thus be applicable to our local population. Patients with diabetes, CKD, and poorer NYHA status exhibited higher mortality rates.